Environmental interpretation of the impact of vehicle emissions on prostate cancer progression - Bingzheng An; Shuo Chen; Chen Zhang; Junyan Wang; Zhaoxin Guo; Ze Gao (Cancer Cell International)
Abstract Objective Vehicle emissions (VEs) are considered important causes of air pollution in cities. This study aims to analyze the role of VEs in the progression of prostate cancer (PCa). Methods We used the CTD database to obtain genes associated with VEs in prostate cancer to explore the associations between VEs and prostate cancer. LASSO regression analysis was subsequently used to construct a novel VEs-related progression model in the TCGA and GEO databases. Differences in the progression-free interval (PFI), clinical characteristics and immune characteristics were compared among patients with different VEs score. Finally, we confirmed that the changes of DNMT3B after VEs mediation and that DNMT3B promoted the progression of prostate cancer by preliminary experiments. Results The analysis of VEs-enriched diseases revealed the most significant enrichment in the prostate cancer pathway. The GO enrichment analysis observed that VEs affected multiple signaling pathways and biological processes in PCa. On the basis of VEs-associated genes, we relied on the VEs scoring model to accurately evaluate the PFI (p < 0.05). In patients with high VEs scores, tumor mutation burden (TMB) (R = 0.29, p < 0.001) and the cytolytic activity (CYT) (R = 0.161, p < 0.001) scores were increased, as was the expression of immunosuppressive ligands. Functional experiments showed that knockdown of DNMT3B inhibited the proliferation, colony formation and migration of prostate cancer cells in vitro. In addition, we found that DNMT3B expression was significantly increased in tumor cells after VEs treatment. Conclusions This study presents unique opinions into the impact of VEs on prostate cancer progression and highlights the need for more in-depth exploration of the mechanistic link between VEs and prostate cancer progression.